Pengaruh Gaya Kepemimpinan dan Kemampuan Beradaptasi terhadap Disiplin Kerja Pegawai : Survei pada Pegawai Kantor Desa Pangliaran Kecamatan Pancatengah Kabupaten Tasikmalaya - Mela G Komara (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to find out how much influence leadership style and adaptability have on employee work discipline in the Pangliaran Village Office, Pancatengah District, Tasikmalaya Regency. The method used in this study is quantitative with a survey approach. With a research sample of 35 people as respondents to the Pangliaran Village Office, Pancatengah District, Tasikmalaya Regency based on 35 known population data. The data used is using primary data. The analysis tool used in this study was multiple linear regression using the SPSS support application version.25. The test results showed that partially showed the variables used in the study, namely leadership style and adaptability, had a significant partial effect on the work discipline of employees at the Pangliaran Village Office, Pancatengah District, Tasikmalaya Regency. Simultaneously, there was a significant influence of leadership style and adaptability to employee work discipline based on multiple linear regression analysis tests obtained a signification of 0.001 where this value was smaller than 0.05. By testing the Coefficient of Determination to get an R Square value of 0.360 or 36%. shows the magnitude of the influence of leadership style and adaptability on employee work discipline and 64% is the influence of other variables beyond the variables used in this study.